SIMULATION OF TRANSPORT AND LOGISTICS SCHEMES OF TRUCK TRANSPORTATION UNDER THE CONDITIONS OF GLOBAL RISKS - Sharko, Oleksandr; Buketov, Andrii; Klevtsov, Kostyantyn; Sapronov, Oleksandr; Akimov, Oleksandr (Problems of Friction and Wear, 2023)
As a result of the increase in the number of factors that ensure the efficiency of transport flows, the methods of building mathematical models, which are based on the consideration of general laws, turned out to be ineffective. Therefore, it is promising to involve experimental methods of identification based on the formalization of the results of observations and analysis of the arrival of new information about changes in the situation that has developed with the use of new digital technologies. The article shows that in the near future, road connections together with water transport will be of key importance, and therefore the task of mathematically ensuring the management of the preservation of traffic flows under the conditions of global risks will always be relevant. The method of work is the modeling of traffic flows under conditions of preservation of global risks. A solution to the problem of maintaining the dynamics of traffic flows caused by the pandemic, military actions and extreme situations is proposed. Based on graph theory, Ford-Falkerson and Dinitz algorithms, a modified algorithm for determining the structure of transportation was developed. A feature of the algorithm is the synchronization of the capacity of transport flows with the moments of lifting and introducing restrictions on transport. The novel proposed algorithm is the possibility of adjusting transport routes. Also, a new use of the proposed modified algorithm is the synchronization of technologies using the methodology of determining the throughput capacity of the branches of the implementation of transport flows with moments of the concept and introduction of restrictions due to unforeseen situations and global risks. The modified algorithm for determining traffic flows in the conditions of unforeseen situations and global risks based on the maximum algorithms of Ford-Falkerson and Dinitz ensures the minimization of losses of carriers and traffic flow. Implementation of the algorithm ensures maximum traffic flow in extreme conditions and global risks.